(untitled) (Bangladesh Journal of Pharmacology, 2017)
High rate of resistance among Staphylococcus infection initiates scientists to discover new antibiotics. The objective of this study is to determine the effect of tannins isolated from the Pimenta dioica leaves on Staphylococcus aureus and methicillin resistant S. aureus as well as to evaluate their effect on hemolysin production. The antimicrobial activity of 4,6-(S)-hexahydroxydiphenoyl-(?/?)-D-glucopyranose and casuarinin, pedunculagin and nilocitin tannins from P. dioica was examined using agar diffusion method. Moreover, minimum inhibitory concentrations were evaluated by microtiter plate assay method. Pedunculagin and nilocitin exhibited antibacterial and anti-hemolytic effect against S. aureus. This will open the era for in vivo assessment of such compounds for clinical applications. Video Clip of Methodology: Method: 8 min 2 sec Full Screen Alternate